2017
DOI: 10.14260/jemds/2017/1410
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology and Bacteriology in Hansen’s Disease

Abstract: BACKGROUND Leprosy is a disease, which has been associated with tremendous social stigma with cases recorded in the Old Testament. It is an infectious disease caused by Mycobacterium leprae. Leprosy expresses itself in different clinicopathological forms depending on the immune status of the patient. Diagnosis of leprosy only on clinical basis is difficult. So, confirmation of diagnosis in leprosy is an important indication for histopathological examination. The parameters used for the histopathological classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
2
0
0
Order By: Relevance
“…Present study shows the histopathologically most common subtypes of leprosy were TT and BT which are similar to the study of Srismitha et al [15], Dhakwa et al [3] and Sushilkumar et al [17]. In study done by Nila Theresa Davis et al [18] BT was the most common subtype found followed by BL.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Present study shows the histopathologically most common subtypes of leprosy were TT and BT which are similar to the study of Srismitha et al [15], Dhakwa et al [3] and Sushilkumar et al [17]. In study done by Nila Theresa Davis et al [18] BT was the most common subtype found followed by BL.…”
Section: Resultssupporting
confidence: 90%
“…Like our study, few studies done by Shushilkumar et al [17] and Davis et al [18] 6+ grade is found in all cases of histoid Hansen's and maximum cases of LL whereas acid fast bacilli were not demonstrated in maximum cases of TT.…”
Section: Resultssupporting
confidence: 73%